Encrypting and decrypting algorithms using strong face graph of a tree. Issue 4 (1st October 2020) - Kuppan, R.; Shobana, L.; Cangul, Ismail Naci
Abstract : The encryption and decryption is based upon the type of cryptographic scheme being employed and also in some form of key. It is most closely associated with the development and creation of the mathematical algorithms used to encrypt and decrypt messages. The combination of graph labelling techniques together with cryptography to encrypt and decrypt the numbers has been already an ongoing aspect of research. In this paper, the concept of face antimagic labelling is used for a strong face of duplication of all vertices by the edges of a tree to encrypt and decrypt 13 secret numbers.